Equilibrio Financiero del Consejo Nacional de Gobiernos Parroquiales Rurales del Ecuador (Conagopare Los Ríos) - Galeas Rebolledo, Edwin Fernando (2017)
This research has the professional character of an undergraduate degree, in order to obtain a degree in Accounting and Auditing, deals with the Financial Balance of the National Council of Rural Parroquial Governments of Ecuador (CONAGOPARE LOS RÍOS). Currently the country is experiencing economic problems, which have directly affected the development of trade and other activities in Ecuador, the budget allocations received by CONAGOPARE LOS RIOS is 2% of the budget of each Rural Parochial GAD of the Province Established in The Organic Code of Territorial Organization, Autonomy and Decentralization, where it mentions in detail and explicit the percentage of the budget that the institutions receive such as the GADPRs, CONAGOPARE PROVINCIAL and CONAGOPARE NACIONAL. The National Council of Rural Parochial Governments of Ecuador (CONAGOPARE LOS RÍOS) is an entity dedicated to represent to watch, and to give permanent advice to the seventeen Autonomous Decentralized Rural Parochial Governments that belong to the province of the Rivers. Attached to the regulations in force and complying with the National Plan for Good Living, and other relevant laws promoting development and generating benefits for the RURAL population. The research was focused on the functioning and performance of the financial department, so I knew the problems triggered by the economic crisis in Ecuador and the measures they took to deal with this situation. Giving truth to the results obtained and the relative importance of the budget information. Within this case study, the methodology that was used to obtain information that was necessary and important for the accomplishment of this work was specified. 2 aims to publicize the factors that influenced the financial balance in CONAGOPARE DE LOS RIOS. Interview Ms. Celia Espinoza treasurer, CONAGOPARE (LOS RIOS), and each of the treasurers of the different Parish GAD Rural of the Province of Los Ríos, through which I obtained information from the Institution, also by this method was interpreted the version of the people involved in the development of this case study.